2020
DOI: 10.1155/2020/3418398
|View full text |Cite
|
Sign up to set email alerts
|

PLOD1 Is a Prognostic Biomarker and Mediator of Proliferation and Invasion in Osteosarcoma

Abstract: Objective. Osteosarcoma is the most common primary bone tumor and most frequently develops during adolescence. PLOD family was mainly involved in lysyl hydroxylation and rarely investigated in cancers, especially in osteosarcoma. The aim of this study was to investigate the expression pattern and oncogenic role of PLODs in osteosarcoma. Methods. GEO datasets (GSE16088, GSE33382, and GSE16091) and validation cohort were used to analyze the expression pattern of PLODs in osteosarcoma. Kaplan-Meier survival analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Considering the essential role of PLOD3, and the encoded enzyme, in the formation of the extracellular matrix derived from fibroblasts, chondroblasts and osteoblasts, we were not surprised that it could also be overexpressed in connective tissue malignancies (SARC), compared to corresponding normal tissue, according to the immunohistochemical analyses. Considering the findings of Jiang et al, that PLOD1 is a prognostic marker in osteosarcomas [ 68 ]. Further studies, especially of soft tissue sarcomas, are pending.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the essential role of PLOD3, and the encoded enzyme, in the formation of the extracellular matrix derived from fibroblasts, chondroblasts and osteoblasts, we were not surprised that it could also be overexpressed in connective tissue malignancies (SARC), compared to corresponding normal tissue, according to the immunohistochemical analyses. Considering the findings of Jiang et al, that PLOD1 is a prognostic marker in osteosarcomas [ 68 ]. Further studies, especially of soft tissue sarcomas, are pending.…”
Section: Discussionmentioning
confidence: 99%
“…Deposition and cross-linking of collagen within the ECM offer a chemical and physical support for tumor formation and proliferation (Qi and Xu, 2018). Three members of the PLOD family (i.e., PLOD1, PLOD2, and PLOD3) leading to cancer progression and metastasis when dysregulated have already been identified (Jiang et al, 2020;Li S. S. et al, 2020). It has recently been recognized that PLOD1 is overexpressed in glioma (Tian et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of both PLOD1 mRNA and protein in clear cell renal cell carcinoma (ccRCC) tissues was significantly higher than that in normal kidney tissues; further studies showed that the increased PLOD1 mRNA level was relate to high pathological grade, advanced tumor stage, shorter progression-free and overall survival rate [31]. PLOD1 expression was increased in osteosarcoma tissues, which was closely linked to distance metastasis and Enneking stage, and worse prog-nosis; silencing of PLOD1 resulted in obvious inhibitions on cell growth, movement, and invasiveness of MG-63 cells and U-2OS cells [20,32]. In the current study, we used plasmids and shRNAs to upregulate and downregulate PLOD1 expression in GC cells AGS and HGC-27 with medium It has been well documented that tumor cells can obtain adequate energy through metabolic stress to meet the rapid growth of tumor cells, including GC [33,34].…”
Section: Discussionmentioning
confidence: 99%